Metacognitive Skills of Junior High School Students in a Pandemic Period Based on the Enriched Virtual Model of PjBL - Nafi’ah, Elisa Rohimatun; Purwanti, Elly; Permana, Fendy Hardian; Fauzi, Ahmad (Universitas Pendidikan Ganesha, 2022)
Currently, the Covid-19 pandemic has become a significant problem faced by the world of education. The presence of Covid-19 has affected the teaching and learning process in various countries. Almost all countries implement physical distancing policies so that many schools are forced to replace face-to-face learning with online learning based on information and communication technology. The limitations of face-to-face activities in online learning are an obstacle for education, especially in the pandemic era. Moreover, the development of science and technology in the 21st century provides new challenges for the world of education, requiring students to have cognitive skills and metacognitive skills. This quantitative study investigates the effect of the project-based learning-based enriched virtual learning model on students' metacognitive skills. The research design was quasi-experimental with a nonequivalent control group design involving 40 students (22 male students and 18 female students) in class VII. Metacognitive skills were measured using a metacognitive rubric. Data collection is done by using pre-test, post-test, and assignment. Successively, the test used to analyze the metacognitive skills data was One-Way ANCOVA. The results showed that the project-based learning-based enriched virtual learning model significantly affected metacognitive skills (Sig = 0.000). Overall, students got a very memorable experience when following the learning stages so that the model can be used as a reference for use in the following science lesson.